2015
DOI: 10.1021/acs.jpca.5b03503
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Screening Approach for the Discovery of Lignin Polymer Breaking Pathways

Abstract: The directed depolymerization of lignin biopolymers is of utmost relevance for the valorization or commercialization of biomass fuels. We present a computational and theoretical screening approach to identify potential cleavage pathways and resulting fragments that are formed during depolymerization of lignin oligomers containing two to six monomers. We have developed a chemical discovery technique to identify the chemically relevant putative fragments in eight known polymeric linkage types of lignin. Obtainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 83 publications
(181 reference statements)
2
20
0
Order By: Relevance
“…Only cleavage at bonds D or E corresponds to single homolytic bond cleavage, whereas the opening of the five-membered ring results in significant rearrangement after formation of a radical. This latter observation is consistent with our earlier studies of the ring-opening in the β-β and β-5 dimers 59 . We thus characterize the eight cleavage pathways in terms of bonds cleaved that lead to a final product distribution.…”
Section: A Overview Of Spirodienone Cleavage Pathwayssupporting
confidence: 94%
See 1 more Smart Citation
“…Only cleavage at bonds D or E corresponds to single homolytic bond cleavage, whereas the opening of the five-membered ring results in significant rearrangement after formation of a radical. This latter observation is consistent with our earlier studies of the ring-opening in the β-β and β-5 dimers 59 . We thus characterize the eight cleavage pathways in terms of bonds cleaved that lead to a final product distribution.…”
Section: A Overview Of Spirodienone Cleavage Pathwayssupporting
confidence: 94%
“…In all cases, however, the homolytic ring-opening cleavage of bond C occurs followed by a number of different events that depend upon the AP topology. This observation highlights the benefit of sampling of AP choices as a means to discover depolymerization pathways, as we have previously observed in other lignin motifs 59 .…”
supporting
confidence: 76%
“…The diversity of the monomer (oligomer) coupling and polymerization mechanisms makes the study of this polymer a difficult task (Boerjan et al, 2003 ). The breaking pathways of lignin (Mar et al, 2015 ) are of great interest since it has been found as one of the principal responsible for biomass recalcitrance in biofuel production (Batalha et al, 2015 ). Lignin varies between species and also between cellular types inside the same tree/plant (Campbell and Sederoff, 1996 ; Neutelings, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Computational approaches to complement available structural data have yielded insights with respect to lignin interaction with its immediate biological environment, , its thermal degradation, or chemical modification and solvation. , However, these simulations often use a homogeneous lignin polymer, which is not representative of heterogeneous lignin synthesis products that demonstrate wide variation in size and composition. , To model this morphological diversity, recent work has developed lignin topological libraries that emulate the distributions of sizes and linkages seen in isolated lignin populations. , …”
Section: Introductionmentioning
confidence: 99%